Stage and cancer-specific mortality differ within specific Asian ethnic groups for upper tract urothelial carcinoma: North American population-based study - Collà Ruvolo, Claudia; Würnschimmel, Christoph; Nocera, Luigi; Wenzel, Mike; Tian, Zhe; Shariat, Shahrokh F; Saad, Fred; Verze, Paolo; Imbimbo, Ciro; Briganti, Alberto; Mirone, Vincenzo; Karakiewicz, Pierre I (International journal of urology, 2021)
OBJECTIVES: To examine the effect of specific Asian ethnic subgroups on stage at presentation and cancer-specific mortality in non-metastatic upper tract urothelial carcinoma among North American upper tract urothelial carcinoma Asian patients treated with radical nephroureterectomy. METHODS: We relied on the Surveillance, Epidemiology and End Results database, from 2004 to 2016. Kaplan-Meier plots and multivariable Cox regression models predicting cancer-specific mortality were used. RESULTS: Of 584 upper tract urothelial carcinoma patients, 173 (29.6%) were Chinese versus 130 (22.3%) Japanese versus 68 (11.6%) Korean versus 64 (11.0%) Filipino versus 40 (6.8%) Vietnamese versus 109 (18.7%) other. Vietnamese and Chinese patients showed the highest rates of T4 N0 M0 and/or T1-4 N1-2 M0 (25.0% and 18.5%, respectively), relative to other Asian ethnic subgroups. In Kaplan-Meier plots, Vietnamese patients showed the highest cancer-specific mortality rate. In multivariable models, Vietnamese ethnicity also independently predicted higher cancer-specific mortality (hazard ratio 2.15, P = 0.02 and hazard ratio 1.96, P = 0.03), relative to Japanese and Chinese patients. All other Asian ethnic subgroups showed similar cancer-specific mortality patterns. CONCLUSION: Vietnamese and Chinese patients are at a stage disadvantage at upper tract urothelial carcinoma diagnosis, relative to all other Asian ethnicities. After adjustment for stage, only Vietnamese patients showed a survival disadvantage relative to all other Asian ethnic subgroups. As a result, it appears that Vietnamese patients not only present at a higher upper tract urothelial carcinoma stage, but additionally appear to harbor upper tract urothelial carcinoma that progresses at a faster rate than in other Asian ethnic subgroups.
Keywords: Chinese; North America; Humans; Severní Amerika; karcinom z přechodných buněk; Surveillance; Ethnicity; lidé; ethnicity; survival; Epidemiology and End Results database; Ureteral Neoplasms; nádory močového měchýře; Retrospective Studies; Carcinoma, Transitional Cell; etnicita; retrospektivní studie; race; nádory močovodu; Urinary Bladder Neoplasms